PENGARUH KECEMASAN MATEMATIKA (MATHEMATICS ANXIETY) TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS VII MTs - Lestari, Hesti; Fitriza, Rozi; A, Halen (Math Educa Journal, 2020)
This article discusses the differences in students' mathematical problem solving skills based on their level of mathematical anxiety, and the effect of mathematical anxiety on their mathematical problem solving skills. The instruments used in this study were mathematics anxiety questionnaires and mathematics problem solving ability tests. The data were analyzed by two-way ANOVA. The results of this study shows that: there are differences in students' mathematical problem solving skills at the anxiety level of the low, medium and high categories; and there is a negative influence of mathematics anxiety on the ability to solve mathematical problems with an influence value of 86.3%.